Understanding food insecurity risk in the United States: A longitudinal analysis - Seth A. Berkowitz; Hilary K. Seligman; Deepak Palakshappa (Elsevier, 2024)
Background: Food insecurity, lack of consistent access to the food needed for an active, healthy life, harms population health. Although substantial biomedical evidence examines the connections between food insecurity and health, fewer studies examine why food insecurity occurs. Methods: We propose a conceptual understanding of food insecurity risk based on institutions that distribute income-the factor payment system (income distribution stemming from paid labor and asset ownership), transfers within households, and the government tax-and-transfer system. A key feature of our understanding is 'roles' individuals inhabit in relation to the factor payment system: child, older adult, disabled working-age adult, student, unemployed individual, caregiver, or paid laborer. A second feature is that the roles of others in an individual's household also affect an individual's food insecurity risk. We tested hypotheses implied by this understanding, particularly hypotheses relating to role, household composition, and income support programs, using nationally-representative, longitudinal U.S. Current Population Survey data (2016-2019). Results: There were 16,884 participants (year 1 food insecurity prevalence: 10.0%). Inhabiting roles of child (Relative Risk [RR] 1.79, 95% Confidence Interval [95%CI] 1.67 to 1.93), disabled working age-adult (RR 3.74, 95%CI 3.25 to 4.31), or unemployed individual (RR 3.29, 95%CI 2.51 to 4.33) were associated with a greater risk of food insecurity than being a paid laborer. Most food insecure households, 74.8%, had members inhabiting roles of child or disabled working age-adult, and/or contained individuals who experienced job loss. Similar associations held when examining those transitioning from food insecurity to food security in year 2. Conclusions: The proposed understanding accords with the pattern of food insecurity risk observed in the U.S. An implication is that transfer income programs for individuals inhabiting roles, such as childhood and disability, that limit factor payment system participation may reduce food insecurity risk for both those individuals and those in their household.